Pengaruh Besaran Fee Audit, Rotasi Kap, dan Ketepatan Waktu Terhadap Kualitas Audit (Studi Kasus pada Kantor Akuntan Publik di Kota Malang) - Farrel Alvis Marcelino Sitompul; Intan Lifinda Ayuning Putri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The current economic climate makes the availability of valid and reliable financial statements a crucial foundation for stakeholders—such as the government, creditors, and investors—in formulating logical and unbiased economic decisions. This study examines the effects of audit fee levels, public accounting firm rotation, and timeliness on audit quality at public accounting firms in Malang. This research employs a quantitative approach using multiple linear regression analysis and involves 47 auditors as respondents through a questionnaire survey. The results indicate that, both simultaneously and individually, audit fees, CPA firm rotation, and timeliness have a positive and significant impact on audit quality. These findings suggest that adequate compensation mechanisms, consistent implementation of auditor rotation, and adherence to timely reporting can enhance the independence, effectiveness, and efficiency of the audit process. These results reinforce the relevance of Agency Theory by reducing information asymmetry between principals and agents